2011
DOI: 10.3109/00365513.2011.604132
|View full text |Cite
|
Sign up to set email alerts
|

High serum ACE activity predicts severe hypoglycaemia over time in patients with type 1 diabetes

Abstract: In type 1 diabetes individual serum ACE activity is reproducible over time. High ACE activity predicts recurrent SH over at least 40 months with no differences between genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Only few studies explore the rate of severe hypoglycemia and risk factors over a longer period than 1 year. 8,9 These long-term studies find unaltered 9 or increased 8 rates of severe hypoglycemia in contrast to the declining rate in our study. We speculate that the reduced rate in our cohort is explained by the constant focus on problematic hypoglycemia in our diabetes outpatient clinic during the study period.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Only few studies explore the rate of severe hypoglycemia and risk factors over a longer period than 1 year. 8,9 These long-term studies find unaltered 9 or increased 8 rates of severe hypoglycemia in contrast to the declining rate in our study. We speculate that the reduced rate in our cohort is explained by the constant focus on problematic hypoglycemia in our diabetes outpatient clinic during the study period.…”
Section: Discussioncontrasting
confidence: 81%
“…Several risk factors for severe hypoglycemia are known and described in previous studies, for example, impaired hypoglycemia awareness, long duration of diabetes, strict glycemic control and loss of endogenous insulin production (undetectable C-peptide). 4-7 However, the majority of these studies are short-term studies lasting 1 year or less except 2 older studies 8,9 with a follow-up of 3-14 years. Patients’ state of awareness is crucial to perceive and react to hypoglycemia and remains relatively constant during a 1-year period.…”
mentioning
confidence: 99%
“…This has consistently been shown in seven studies in five different cohorts by four independent research groups. [1][2][3][4][5][6][7] One study reported an additive effect of presence of three RAS components -high serum ACE activity, high plasma angiotensinogen concentration and homo-or heterozygosity for the A-allele of the X chromosome-located angiotensin-II receptor subtype 2 1675G/A polymorphism -on the risk of severe hypoglycaemia in type 1 diabetes. 8 This finding suggests that increased angiotensin II receptor subtype 1 activation that is not counterbalanced by subtype 2 activation is detrimental during hypoglycaemia in subjects with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…We previously speculated whether genetic factors are implicated and reported a high rate of severe hypoglycaemia in type 1 diabetic subjects carrying the common deletion-allele of the angiotensin-converting enzyme (ACE) gene that confers high enzyme activity in blood and tissues (9). This finding has been reproduced in six studies in five different populations by four independent research groups (10, 11, 12, 13, 14, 15). Schouwenberg and coworkers showed in healthy adults that possessing the Arg Arg (vs the Gly Gly) polymorphism of the β2-adrenergic receptor may to some extent protect against the development of hypoglycaemia unawareness (16, 17), a major risk indicator of severe hypoglycaemia.…”
Section: Introductionmentioning
confidence: 55%
“…The only hitherto consistently reported biomarkers of severe hypoglycaemia in type 1 diabetes are undetectable C-peptide levels (9, 4), low HbA1c (40, 41, 42) and high serum ACE activity (10, 11, 12, 13, 14, 15). However, these markers only explain a minor proportion of the risk variation between subjects.…”
Section: Discussionmentioning
confidence: 99%